Laser Lap Welding of Thermoplastic Plates : 3rd Report, Discussions on Welding Conditions by Means of Numerical Simulation - HASEGAWA, Tatsuya; TAKAI, Yuichiro; DOI, Shintaro; NAKAMURA, Takashi; MAEDA, Tomohiro (Transactions of the Japan Society of Mechanical Engineers Series C, 2002)
Laser lap welding of PMMA was numerically simulated on the basis of heat transfer equation. When the laser energy was converted into heat only at the transparent/opaque thermoplastic interface, the energy flux necessary for a fixed temperature increase was proportional to the -0.5 power of the irradiation time of laser. This relation was exactly the same as that predicted by dimensional analysis, while it was different from the experimental results with a power index of -0.7. When the laser energy was absorbed and converted into heat in the opaque thermoplastic plate and radiated from the interface, the energy flux became close to the experimental data and proportional to the -0.7 power of the irradiation time.